Aspergillus niger: an unusual cause of invasive pulmonary aspergillosis - Person, A. K. (Society for General Microbiology, 2010)
Infections due to Aspergillus species cause significant morbidity and mortality. Most are attributed to Aspergillus fumigatus, followed by Aspergillus flavus and Aspergillus terreus. Aspergillus niger is a mould that is rarely reported as a cause of pneumonia. A 72-year-old female with chronic obstructive pulmonary disease and temporal arteritis being treated with steroids long term presented with haemoptysis and pleuritic chest pain. Chest radiography revealed areas of heterogeneous consolidation with cavitation in the right upper lobe of the lung. Induced bacterial sputum cultures, and acid-fast smears and cultures were negative. Fungal sputum cultures grew A. niger. The patient clinically improved on a combination therapy of empiric antibacterials and voriconazole, followed by voriconazole monotherapy. After 4 weeks of voriconazole therapy, however, repeat chest computed tomography scanning showed a significant progression of the infection and near-complete necrosis of the right upper lobe of the lung. Serum voriconazole levels were low–normal (1.0 μg ml(−1), normal range for the assay 0.5–6.0 μg ml(−1)). A. niger was again recovered from bronchoalveolar lavage specimens. A right upper lobectomy was performed, and lung tissue cultures grew A. niger. Furthermore, the lung histopathology showed acute and organizing pneumonia, fungal hyphae and oxalate crystallosis, confirming the diagnosis of invasive A. niger infection. A. niger, unlike A. fumigatus and A. flavus, is less commonly considered a cause of invasive aspergillosis (IA). The finding of calcium oxalate crystals in histopathology specimens is classic for A. niger infection and can be helpful in making a diagnosis even in the absence of conidia. Therapeutic drug monitoring may be useful in optimizing the treatment of IA given the wide variations in the oral bioavailability of voriconazole.